FRI0253 Patient-reported outcomes in patients with rheumatoid arthritis treated with subcutaneous tocilizumab compared with placebo or intravenous tocilizumab in combination with csdmards. (15th June 2017) - Strand, V; Lampl, K; Birchwood, C; Pei, J; Tuckwell, K; Finch, R; Kivitz, A; Burmester, G
Abstract : Background: Two previous randomized, controlled trials (RCTs), BREVACTA and SUMMACTA, showed subcutaneous tocilizumab (TCZ-SC) was superior to placebo (PBO) and comparable to intravenous TCZ (TCZ-IV) in combination with csDMARDs for improving RA disease activity. 1, 2 Objectives: To compare the efficacy of TCZ-SC with PBO or TCZ-IV + csDMARDs for improvement in patient-reported outcomes (PROs) in 2 RCT populations. Methods: Both RCTs enrolled patients (pts) with inadequate responses to DMARDs; up to 20% had inadequate responses to tumor necrosis factor inhibitors. In BREVACTA, pts received blinded TCZ-SC 162 mg or PBO every 2 weeks (q2w) + csDMARDs for 24 weeks. In SUMMACTA, pts received TCZ-SC 162 mg weekly or TCZ-IV 8 mg/kg q4w + csDMARDs for the 24-week double-blind period. PROs, assessed at 12 weeks (prior to rescue) in BREVACTA and 24 weeks in SUMMACTA, included patient global assessment (PtGA; visual analog score [VAS], 0–100 mm), pain (VAS), Health Assessment Questionnaire Disability Index (HAQ-DI, 0–3) and Short Form-36 (SF-36) physical and mental component summary (PCS, MCS: 0–50) and domain (0–100) scores. The proportions of pts reporting scores ≥ minimum clinically important differences (MCID) and ≥ age/gender-matched normative values were assessed for each treatment group. Results: Baseline PRO scores were mostly comparable between treatment groups in each study and between study populations. In BREVACTA, significantly more pts who received TCZ-SC reported scores ≥ MCID for all PROs at week 12 compared with PBO (54% to 73% vs 42% to 55%, respectively; number needed to treat [NNT], 5.2 to 13.0). Compared with 1% to 20% at baseline, 8% to 34% of pts who received TCZ-SC and 4% to 25% of PBO pts reported scores ≥ normative values in all PROs at week 12 (Table). In SUMMACTA, similar proportions of pts who received TCZ-SC and TCZ-IV reported scores ≥ MCID in all PROs at week 24 (61% to 84% vs 64% to 84%, respectively). The proportion of patients who reported scores ≥ normative values was comparable between the TCZ-SC and TCZ-IV groups across all PROs; compared with 0.2% to 23% at baseline, 14% to 41% of pts who received TCZ-SC and 15% to 42% of pts who received TCZ-IV reported scores ≥ normative values at week 24 (Table). Conclusions: In BREVACTA, TCZ-SC + csDMARDs resulted in significantly greater improvements across all PROs and significantly more pts reporting scores ≥ MCID at week 12 compared with PBO. Similarly, more pts receiving TCZ-SC reported scores ≥ normative values at week 12 compared with PBO, despite few pts with such scores at baseline. Responses were similar between pts treated with TCZ-SC and TCZ-IV + csDMARDs in SUMMACTA at week 24. These data show TCZ treatment resulted in clinically meaningful improvements in PROs and indicate that attainment of normative scores is a realistic goal in treatment of pts with active RA. References: Kivitz A, et al. Arthritis Care Res (Hoboken). 2014;66:1653–61. Burmester G, et al. Ann Rheum Dis. 2014;73:69–74. Acknowledgements: This study was funded by F. Hoffmann-La Roche/Genentech. Disclosure of Interest: V. Strand Consultant for: Abbvie; Amgen; AstraZeneca; Biogen Idec; Boehringer Ingelheim; Celltrion; Crescendo; Genentech/Roche; GlaxoSmithKline; Janssen; Lilly; Merck; Novartis; Pfizer; Regeneron; Samsung; Sanofi; UCB, K. Lampl Employee of: Genentech, Inc, C. Birchwood Employee of: Genentech, Inc, J. Pei Employee of: Genentech, Inc, K. Tuckwell Shareholder of: Roche, Employee of: Roche, R. Finch Shareholder of: Roche, Employee of: Roche, A. Kivitz Consultant for: Genentech; Novartis; Pfizer; Sanofi-Regeneron; UCB, G. Burmester Grant/research support from: Roche, Consultant for: Roche